The Effect of Rainfall and Temperature on Honey Production Evidence from Libya - Intisar Mohamed; Fouzi Faraj (AlQalam Journal of Medical and Applied Sciences, 2022)
Aims. The paper aimed to investigates the effect of rainfall and temperature on honey production. Methods. An Autoregressive Distributed Lag (ARDL) modeling is employed by using annual data over the period of 1990-2013. Results. Bounds test results reveal that there is co-integration between study variables under investigation. Also, the study results indicate a positive effect and significantly of temperature and a negative and non-significant of rainfall effect on honey production in long-run. Conclusion. While in short-run, the temperature in lagged one and lagged two has a negative and significant effect on honey production.